2017
DOI: 10.1002/jib.432
|View full text |Cite
|
Sign up to set email alerts
|

Screening of bioactive components in grape and apple vinegars: Antioxidant and antimicrobial potential

Abstract: Vinegars contain several bioactive compounds that are characterized according to the type of the raw material, such as grape vinegars and apple vinegars. Liquid chromatography coupled to diode array detection and electrospray ionization tandem mass spectrometry was used for identification and quantification of phenolic compounds. Antioxidant properties of vinegars were determined by 2,2‐diphenyl‐1‐picrylhydrazyl and 2,2′‐azino‐bis‐3‐ethylbenzthiazoline‐6‐sulphonic acid assays. Antimicrobial activities of vineg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 31 publications
6
43
0
Order By: Relevance
“…On the other hand, according to the results obtained in the present work, the vinegar aging process in contact with wood seems to have not influenced in the content of phenolic acids quantified. Concerning the levels of individual phenolic acids quantified in the vinegars samples analyzed, syringic and caffeic acids were the most abundant, which is in accordance with previous data reported by other authors for grape vinegars (Kelebek et al, 2017) and apple vinegars (Nakamura et al, 2010). Budak and Guzel-Seydim (2010) also reported higher content of chlorogenic and syringic acids for wine vinegars, while other authors (Bakir et al, 2017) reported higher content of p-coumaric and caffeic acids for different fruit vinegars.…”
Section: Table Vsupporting
confidence: 81%
See 4 more Smart Citations
“…On the other hand, according to the results obtained in the present work, the vinegar aging process in contact with wood seems to have not influenced in the content of phenolic acids quantified. Concerning the levels of individual phenolic acids quantified in the vinegars samples analyzed, syringic and caffeic acids were the most abundant, which is in accordance with previous data reported by other authors for grape vinegars (Kelebek et al, 2017) and apple vinegars (Nakamura et al, 2010). Budak and Guzel-Seydim (2010) also reported higher content of chlorogenic and syringic acids for wine vinegars, while other authors (Bakir et al, 2017) reported higher content of p-coumaric and caffeic acids for different fruit vinegars.…”
Section: Table Vsupporting
confidence: 81%
“…Individual phenolic acids of the commercial red wine vinegars studied .0 mg/L, respectively), while RV2 sample showed the lowest value (1.33 mg/L).Phenolic acids quantified from the commercial red wine vinegars samples studied were in general in accordance with previous data published by Natera et al (2003) and Cerezo et al (2008), but lower than values obtained by Kelebek et al (2017). On the other hand, according to the results obtained in the present work, the vinegar aging process in contact with wood seems to have not influenced in the content of phenolic acids quantified.…”
Section: Table Vsupporting
confidence: 79%
See 3 more Smart Citations